MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN MENGGUNAKAN MEDIA KARTU KATA PADA SISWA KELAS II SDN 114/VII BUKIT KALIMAU ULU KECAMATAN BATANG ASAI KABUPATEN SAROLANGUN TAHUN AJARAN 2022/2023" - Wiwik Purwasih (Jurnal Ilmiah Pendidikan Dasar (JIPDAS), 2023)
This research was conducted in grade 2 of Public Elementary School Number 114/VII Bukit Kalimun Ulu, Batang District, Sarolangun Asai Regency, 2022/2023 Academic Year. The implementation of the research consisted of the planning, implementation, data collection, reflection, and re-planning stages. The method used is descriptive qualitative method. The research subjects were grade II students at SDN No. 114/VII Kalimau Ulu Hill, Batang Asai District. The object in this study is the use of word card media. Implementation of learning improvement In this study used 2 cycles. Each cycle consists of 4 stages: planning, implementation, observation/data collection, and reflection. The results showed that data from 11 students (100%) had scored above the KKM. 4 students (36.36%) got a very good grade, and 7 students (63.63%) got a good mark. Meanwhile, there were no students (0%) who scored less and failed. This percentage indicates that the learning process in improving the ability to write narratives using the card media method in cycle 2 has taken place optimally and there is no need for further improvement cycles.